Buryat Traditional Wrestling With Past And Present Codes: Buhe-Barildaan - Turkmen, Mehmet (Lahore Medical Research Center Llp, 2021)
Background: Buryats, the ancient homeland of all Turkic peoples before Central Asia and living in Southern Siberia, are the first peoples with whom they interact in Turkish-Mongolian culture and genetic codes. Buryats have a traditional wrestling called Buhe-Barildaan, which they attach great importance to since ancient times. Aim: For a foreigner, understanding Buryat traditional wrestling will undoubtedly shed light on other aspects of the social life of Buryats and even Turkish-Mongolian peoples. Therefore, the study aims to explain 'Buhe-Barildaan' with its formation, transformation and rituals. Methods: In addition to the literature review, descriptive research and comparison method, one of the models in the qualitative approach, was used. The research is limited to the folkloric wrestling of Buryats, who live in Southern Siberia and consist of Turkish-Mongolian genetics. Results: Two types of Buryat 'Buhe-Barildaan' wrestling, namely 'Forest' and 'Steppe' style, were determined. First of all, 'forest-type' wrestling has become widespread among Turkish origin Oyrat, Bulaga and Ehiri Buryats and Mongolian origin Onon Buryats. Now practiced almost everywhere, the steppe-type was seen only in people dealing with animal husbandry. In steppe-type wrestling matches, one of the three organs that touches the floor of one of the opponents ends in defeat. Conclusion: It was seen that non-Russian native authors used various suggestion methods to explain the importance of Buryat wrestling, to suggest its continuity among social indicators, to create social meaning and national identity. Buryat wrestling culture, it is based on the economic life unique to the development and continuity of the people and the traditional sources of the geographical environment that feed this life. Buhebarildaan wrestling is one of the most important elements of the sports culture that helps to preserve the national identity and connection between generations. The functional and ideological origins of the Buryat Buhe-barildaan wrestling, historically, it is associated, first of all, with the choice of a mass who, besides having to face external power, is the leader of the military forces. In addition, Buhe-barildaan wrestling, which has two types, namely steppe and forest types, was seen to coincide with the wrestling of the peoples living in those geographies, especially Turks, in the context of typology and homogeneity.
Keywords: Buryat identity; Wrestling culture; Buhe-Barildaan